Video documental sobre la vida del Oso de Anteojos en la sierra centro-norte del Ecuador- - Giacometti Burbano, Paola Fernanda (Quito;2013, 2013)
This documentary is a educational and communicational product with huge scope above various fields in the society, seeking interests and sensitization to the different problematic that encompass the ecosystem and its maintenance. In terms of theoretical analysis aims to establish a relation of contradiction between Latin American view of communication, in front of concepts that fundament the modernity and its goal of extractive development, to understand the debate between communication and ecosystem. The observation for this experience implied collecting data and testimonies in geographical zones were this species lives and its relations with community members to establish clear criteria about the problematic and its elements.